Kant's 'groundwork of the metaphysics of morals - Timmermann, Jens (New York: Cambridge university press, 2013)
Discusses Kant's philosophical development in the Groundwork and his attempt to justify the categorical imperative as a principle of freedom.
Chapter 1 Ethics and anthropology in the development of Kant's moral philosophy; Chapter 2 Happiness in the Groundwork; Chapter 3 Acting from duty: inclination, reason and moral worth; Chapter 4 Making the law visible: the role of examples in Kant's ethics; Chapter 5 The moral law as causal law; Chapter 6 Dignity and the formula of humanity; Chapter 7 Kant's kingdom of ends: metaphysical, not political; Chapter 8 Kant against the 'spurious principles of morality' Chapter 9 Autonomy and impartiality: Groundwork III Chapter 10 Problems with freedom: Kant's argument in Groundwork III and its subsequent emendations; Chapter 11 Freedom and reason in Groundwork
Includes bibliographical references and index.
Keywords: Ethics; Kant, Immanuel, 1724-1804.